2017
DOI: 10.1097/mao.0000000000001339
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hearing Results After Ossiculoplasty

Abstract: The OOPS index makes it possible to accurately prognosticate hearing outcomes in adult and pediatric patients undergoing ossiculoplasty in both the short term and the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
3
19
2
Order By: Relevance
“…Previous studies regarding cholesteatoma surgery were heterogenous and included both CWU and CWD mastoidectomies, 12,16-20 primary and revision procedures, 19,20 and pediatric and adult populations. 19-21 Moreover, ossiculoplasty comparison in this group of patients as a single-stage procedure after tympanomastoidectomy has yet to be discussed in the literature.…”
Section: Introductionsupporting
confidence: 92%
“…Previous studies regarding cholesteatoma surgery were heterogenous and included both CWU and CWD mastoidectomies, 12,16-20 primary and revision procedures, 19,20 and pediatric and adult populations. 19-21 Moreover, ossiculoplasty comparison in this group of patients as a single-stage procedure after tympanomastoidectomy has yet to be discussed in the literature.…”
Section: Introductionsupporting
confidence: 92%
“…Short-term and long-term ossiculoplasty results however can vary significantly [Yu et al, 2013], and poor long-term results are caused by various factors with extrusion and displacement being most common. Moreover, patients who underwent ossiculoplasty very often require a conventional hearing aid (cHA) even after surgery [Cox et al, 2017;De la Cruz and Teufert, 2003]. The additional use of cHAs may be suitable to treat the sensorineural component of the hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The overall success rate for ossiculoplasty at threshold for success <20 db HL was lower than most other studies have reported. 14,15 We speculate that this may be because we based success on a postoperative audiogram done 3 months postoperatively, which was earlier than most other studies have reported, as audiograms 1 year after surgery were often not available to us, and this finding may reflect persistent middle ear effusion postoperatively. There was also a large number of patients in our study who had undergone previous surgeries, which may predispose to ossiculoplasty failure due to damage to stapes and oval window structures from surgery or disease as well chronic changes of the middle ear spaces from long-term chronic otitis media and cholesteatoma.…”
Section: Discussionmentioning
confidence: 93%